Advancing bacteriophages as a treatment of antibiotic-resistant bacterial pulmonary infections. Issue 3 (14th May 2022) - Satta, Giovanni; O'Callagharn, Christopher; Clokie, Martha R.J.; Di Luca, Mariagrazia
Abstract : Purpose of review: The current article summarizes the recent advances in the use of bacteriophages to treat pulmonary infections, particularly those caused by Gram-negative drug-resistant bacteria, including Pseudomonas aeruginosa, Acinetobacter baumannii, Klebsiella pneumoniae and Burkholderia species. It provides an updated overview of the current available evidence, with a summary of published clinical cases, case series and clinical trials currently underway. Recent finding Personalized treatment with bacteriophages is still in its infancy in Europe and the USA, despite extensive experience in Eastern countries. However, more patients are expected to be treated with clinical trials in progress and others planned. Summary: Despite very promising initial results and the confirmation of phage safety, there are still many ethical and practical implications to be considered, from the necessary regulatory approval to optimization of dose and route of administration, to developing strategies to tackle bacterial resistance. Patients with cystic fibrosis are a group where phage therapy, if successful, could have a major impact.